Maternal Age, Gestation, and Parturition as Predictor of Uterine Inertia Incidence - Wijaya, Christian; Kurniawan, Joshua; Singgih, Rendy; Firmansyah, Yohanes; Hendsun, Hendsun (Universitas Malahayati, 2024)
ABSTRACT Uterine inertia could cause complications in labor. Knowing the risk factors for uterine inertia is important to since the Maternal Death Rate in Indonesia is relatively high. This study was aimed to determine whether maternal age, gestation, and parturition could be predictors of uterine inertia. This is a cross-sectional study. Data collection was done at “C” General Hospital, West Java, with all pregnant women in their third trimester of pregnancy in January to December 2019 as samples. The statistical analysis used in this study are Independent T-test, Mann Whitney, ROC Curve test, and Pearson Chi-Square with Yates Correction to see statistical associations. Significant correlation was found between the variables of age ≤ 30 years, gestation ≤ 2 pregnancies, and parturition ≤ 2 births with uterine inertia (PR = 1.331; 1.332; 1.315 times, p-value = 0.001). Uterine inertia is affected by risk factors of age ≤ 30 years, gestation ≤ 2 pregnancies, and parturition ≤ 2 births. The results can be used to help health workers in predicting the incidence of uterine inertia so that adequate responses can be provided. Keywords: Gestation, Maternal Age, Parturition, Predictor, Uterine Inertia